QUALITY CHARACTERISTICS OF SNAKEHEAD FISH (Channastriata) NOODLES WITH THE ADDITION OF AGAR-AGAR FLOUR - Dayani, Rahmi; Sumarto, Sumarto; Dewita, Dewita (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
AbstractThis study aims to determine the effect of adding agar-agar flour to the quality of snakehead fish noodles and determine the amount of agar flour in producing the best quality of snakehead fish noodles. The research method was experimental with the processing of snakehead fish wet noodle with the addition of agar-agar (commercial) flour in different quantities. The research design was a completely randomized design (CRD) consisting of 4 treatment levels, without the addition of agar flour (M0), the addition of agar flour 3 g (M1), 5 g (M2), 7 g (M3). Analysis parameters of organoleptic, moisture content, ash, fat, protein, carbohydrates, and crude fiber. The results showed that the addition of agar-agar flour (commercial) had a significant effect on the 95% confidence level of the quality of snakehead fish noodles. The best treatment is agar-agar 5 g (M2) in producing quality characteristics of fish noodles. The noodles have a bright yellow color, distinctive aroma of fish and agar-agar, and chewy texture and elastic, has a savory taste and an agar-agar taste; snakehead fish noodles have 35.62% moisture, 0.51% ash, 12.79% protein, 1.19% fat, 53.35% carbohydrates, and 1.45% fiber. Keywords: agar-agar flour, Channa striata, fish noodles